2018
DOI: 10.1080/14737140.2018.1520096
|View full text |Cite
|
Sign up to set email alerts
|

Managing side effects in adjuvant endocrine therapy for breast cancer

Abstract: Recent improvements in the survival of hormone-responsive breast cancer are strongly associated with therapeutic advances, particularly with the uptake of adjuvant endocrine therapy. Nevertheless, endocrine therapy is also linked with adverse effects that impact quality of life, social function, and adherence to treatment. Areas covered: This review examines the spectrum and consequences of adverse effects of tamoxifen and aromatase inhibitors, and the pharmacological and non-pharmacological approaches to miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 100 publications
1
75
0
1
Order By: Relevance
“…We demonstrate that social media can be effective in rapidly obtaining large numbers of patient responses regarding care issues. Similar to previous studies [ 1 , 7 , 10 , 17 – 19 , 34 39 ], our results demonstrate that most patients (91%) who take ET experience related side effects, and one-third discontinue treatment early. Our findings suggest that online patient communities can be a valuable tool for identifying variables that influence breast cancer patients’ adherence to ET.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We demonstrate that social media can be effective in rapidly obtaining large numbers of patient responses regarding care issues. Similar to previous studies [ 1 , 7 , 10 , 17 – 19 , 34 39 ], our results demonstrate that most patients (91%) who take ET experience related side effects, and one-third discontinue treatment early. Our findings suggest that online patient communities can be a valuable tool for identifying variables that influence breast cancer patients’ adherence to ET.…”
Section: Discussionsupporting
confidence: 91%
“…Intermittent telehealth visits could also address patient decision resolve, as many patients re-visit their commitment to continue ET multiple times throughout the course of treatment [ 2 ]. Patients may benefit from repeated review of both medication benefits, focusing on absolute, rather than relative benefit , as well as the impact on quality of life during the course of therapy [ 2 , 5 , 18 , 19 , 34 , 37 , 42 , 43 , 62 , 63 ], in a way that more passive reminders do not address.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many patients, even when compliant, will still relapse. 32,33 Our increased understanding of immune signaling in tumorigenesis has led the development of multiple immunotherapiescheckpoint inhibitors (CTLA-4, PD-L1), CAR-T therapy, vaccination, etc. 34 These innovative approaches to cancer treatment have proven to be effective in several tumor types but have been largely disappointing in luminal breast cancer.…”
Section: Irf9 Recruitment To Ifit1 Tssmentioning
confidence: 99%
“…These commercially available compounds, belonging to the third generation of AIs, have high specificity for HA without interfering with the biosynthesis of other steroid hormones and, to date, they are the first line endocrine therapy for the treatment of post-menopausal ER + BC. Nevertheless, the complete depletion of estrogen levels in the whole body caused by inhibition of this enzyme leads to the development of various side effects, such as musculoskeletal pain, reduction of bone density, increase of fractures and cardiovascular events [42][43][44][45]. Several studies have shown that third generation AIs, in particular LTZ, are superior to TAM as first-line therapy for advanced BC.…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%